Tailoring of the biomechanics of tissue-regenerative vascular scaffolds - Krynauw, Hugo (Department of Surgery, 2016)
The lack of long term patency of small diameter synthetic vascular grafts currently available on the market has directed research towards improving the performance of these grafts. Improved radial compliance matching and appropriate tissue ingrowth into the graft structure are main goals for an ideal vascular graft. In addition, the use of biodegradable materials offers the promising prospect of leaving behind a near native vessel with no synthetic material remaining. Tissue ingrowth into grafts alters their mechanics. This, combined with a loss of mechanical integrity over time, in the case of biodegradable scaffolds, brings the need to investigate how these changes play out and how to tailor them for optimal graft healing. This project set out to investigate the mechanics of electrospun Pellethane® 2363-80AE (Dow Chemicals) and DegraPol® (ab medica S.p.A) biostable DegraPol® DP0 and biodegradable DegraPol® DP30 scaffolds during in vivo animal studies. DegraPol® DP30 findings were used to investigate the scaffolds' potential use for vascular grafts by means of a finite element graft model. Porous, electrospun scaffolds were manufactured and implanted into two subcutaneous and one circulatory rat models. All studies consisted of four time points, namely 0, 7, 14 and 28 days. Scaffold morphology was characterised, and tissue ingrowth was quantified by histological analysis of explanted samples. Orthogonal, uni-axial tensile testing measured scaffold mechanical response of in-fibre and cross-fibre deformation. Tissue ingrowth brought about considerable changes in biostable DegraPol® DP0 scaffold mechanics. Tensile testing of degradable DegraPol® DP30 scaffolds in their load bearing circumferential direction showed a balance between a loss in mechanical strength and an increase in strength by tissue ingrowth. This resulted in constant radial compliance of 4.47 ± 0.14%/100 mmHg between 80 and 120 mmHg for the four week period predicted with the numerical models. The finite element model based on DegraPol® DP30 scaffold mechanics for 6 mm grafts showed better, i.e. higher, radial compliance than current grafts used clinically (polyethylene terephthalate and expanded polytetrafluoroethylene grafts). This stability in compliance, coupled with good tissue ingrowth is of scientific importance as it shows that highly aligned, porous electrospun DegraPol® DP30 scaffolds are a viable option for vascular grafting to achieve long term graft patency